Pengaruh Akuntansi Forensik, Skeptisme Profesional Auditor dan Pengalaman Audit terhadap Deteksi Fraud - Annisa Rahmawati (2021)
This study aims to analyze the effect of forensic auditing, auditor professional skepticism, and audit experience on fraud detection. Data was collected by distributing questionnaires to respondents. The population in this study are auditors who work in a public accounting firm in Jakarta, with a sample of 100 auditors. The sampling technique used is purposive sampling with the criteria of auditors who are still actively working at the Public Accounting Firm (KAP) in DKI Jakarta and have at least 6 months of experience working at KAP. The data analysis method used multiple linear regression analysis. Partially, the results showed that forensic audit and audit experience had a significant positive effect on fraud detection, while professional auditor skepticism had no significant effect on fraud detection.